Ваёбыж кар: веросъёс, повесть / Лидия Нянькина - Нянькина Лидия Степановна (Удмуртия, 1996)
Экземпляры: Аб (20160407) / Инвентарный номер: 103999 / Цена: 10.00 / Авт.знак: Н 99 / ГРНТИ: 17.82 / ББК: 84(2=664.1)